Effectiveness of school-based child sexual abuse intervention among school children in the new millennium era: Systematic review and meta-analyses - Che Yusof, Ruhana; Norhayati, Mohd Noor; Mohd Azman, Yacob (Frontiers in Public Health, 2022)
Introduction: A school-based child sexual abuse intervention program was developed with the aim to educate the school children to protect them from sexual abuse. The program was evaluated to make sure the intervention was effective in reducing child sexual abuse cases (CSA). This review aimed to determine the effectiveness of the school-based child sexual abuse intervention program in the new millennium era (2000 to 2021) in improving the knowledge, skills, and attitude of school children under 18 years old toward child sexual abuse. Methods: A systematic search was conducted through MEDLINE (PubMed), EBSCO and SCOPUS databases to collect full English articles related to school-based CSA intervention program published from 2000 to 2021. Results: A total of 29 studies from randomized control trial and quasi-experimental from several countries was analyzed. Comparisons within group of pre-post intervention for knowledge, skills, and attitude were measured by standardized mean difference (SMD) and confidence interval (95% CI) of -1.06 (95% CI: -1.29, -0.84), -0.91 (95% CI: -1.20, -0.61) and -0.51 (95% CI: -3.61, 0.58), respectively. Meanwhile for between intervention and control group comparisons, the SMD of knowledge was 0.90 (95% CI: 0.63, 1.18), skills were 0.39 (95% CI: 0.07, 0.71) and attitude was 1.76 (95% CI: 0.46, 3.07). Conclusion: The program was found to be effective in improving the knowledge, skills, and attitude of the students from pre-intervention to post-intervention and between the intervention and control groups.